Evidence for covert baculovirus infections in a Spodoptera exigua laboratory culture - Murillo, Rosa; Hussey, Mark S.; Possee, Robert D. (Journal of General Virology, 2011)
A laboratory culture of Spodoptera exigua was examined to assess covert (latent or persistent) baculovirus infections and spontaneous disease outbreaks. Two nucleopolyhedrovirus (NPV) species were found to be reactivated from a covert state in a laboratory culture of S. exigua to fully lethal forms. These were identified as S. exigua multinucleopolyhedrovirus (SeMNPV) and Mamestra brassicae NPV (MbNPV) using restriction enzyme analysis of purified viral DNA. Sequence data derived from both overtly and covertly virus-infected insects revealed highly conserved sequences for lef-8, lef-9 and polyhedrin gene sequence (98–100 % nucleotide identity to SeMNPV published sequence). By monitoring spontaneous overt infections and quantifying viral DNA (by quantitative-PCR) in asymptomatic individuals over two generations we identified fluctuating trends in viral DNA levels from covert SeMNPV and MbNPV within an S. exigua host population. Virus levels per insect life stage ranged from 3.51±0.101×105 to 0.29±0.036 pg (detection limit at 0.06 pg). Bioassays performed with this culture of larvae showed a differential susceptibility to SeMNPV-like or MbNPV-like viruses, with SeMNPV superinfections being extremely virulent. The data presented has broad implications relating to our understanding of transmission patterns of baculovirus in the environment and the role of covert infections in host–pathogen interaction dynamics.